2009
DOI: 10.1080/10426500902855158
|View full text |Cite
|
Sign up to set email alerts
|

2,4,6-Triphenylpyrylium Cations as Derivatization Reagents for Sulfide Ions Detection in TLC

Abstract: We report a study of the use of 2,4,6-triphenylpyrylium salts as derivatization reagents for the simple detection of sulfide ions in thin-layer chromatography (TLC). The principle of the presented method is based on the transformation of 2,4,6-triphenylpyrylium compounds into the parent thiopyrylium derivatives upon reaction with sulfide ions. The derivatization reaction took place in a tube or directly on the TLC plate before the developing step. As a consequence of the reaction of sulfide with the 2,4,6-trip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The most important advantages of the LN1 and L1 derivatization reagents are their sensitivity and specificity for sulfide ions. Previous studies have shown that pyrylium salts do not react with fluoride, bromide, chloride, iodide, phosphate, sulfate, nitrate, cyanide, acetate, benzoate, MESNA, cysteine, or octanethiol [25][26][27]. Under certain conditions some amines have been reported to react with 4-[p-(N,N-dimethylamino)phenyl]-2,6-diphenylpyrylium to give yellow derivatives ( = 460 nm) [31], however no amines were expected to be present in the tested water samples.…”
Section: Quantitative Analysis Of Sulfide In Water and Selectivitymentioning
confidence: 99%
See 4 more Smart Citations
“…The most important advantages of the LN1 and L1 derivatization reagents are their sensitivity and specificity for sulfide ions. Previous studies have shown that pyrylium salts do not react with fluoride, bromide, chloride, iodide, phosphate, sulfate, nitrate, cyanide, acetate, benzoate, MESNA, cysteine, or octanethiol [25][26][27]. Under certain conditions some amines have been reported to react with 4-[p-(N,N-dimethylamino)phenyl]-2,6-diphenylpyrylium to give yellow derivatives ( = 460 nm) [31], however no amines were expected to be present in the tested water samples.…”
Section: Quantitative Analysis Of Sulfide In Water and Selectivitymentioning
confidence: 99%
“…The addition of acetonitrile into the derivatization mixture is necessary due to the poor solubility of L1 and LN1 in pure water [25][26][27] and the volume of this organic solvent has a clear effect in the yield of the derivatization reaction. In order to optimize the volume of acetonitrile in the derivatization mixture, different volumes of this organic solvent in the range of 0-6 mL were tested.…”
Section: Optimization Of the Derivatization Proceduresmentioning
confidence: 99%
See 3 more Smart Citations